Malay secondary school students' entrepreneurial attitude orientation and entrepreneurial self efficacy : a descriptive study. - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (Asian Network for Scientific Information, 2011)
As the influential factors affecting intention to become an entrepreneur, entrepreneurial attitude orientation and self-efficacy of students have been one of the main focuses of entrepreneurship research. However, there is not enough information on secondary school students’ attitude toward and efficacy of entrepreneurship particularly, in Malaysia. Through a descriptive approach, this study aimed to determine entrepreneurial attitude and entrepreneurial self-efficacy in order to evaluate the entrepreneurship inclination and potential among Malaysian secondary school students. A sample of 2,574 students was randomly selected from three states around Malaysia as the participants of this study. A set of questionnaire was developed based on previous researches to measure students’ entrepreneurial attitude and self-efficacy. The findings indicate that Malay students have a moderately high attitude toward entrepreneurship. More specifically, the students scored high in self-esteem cognition and achievement cognition but low in self-esteem behavior and self-esteem affect. Moreover, the students perceived themselves as moderately capable of establishing new ventures. The implication of the findings and areas for future researches are discussed.